Varhaiskasvatuksen liikuntakasvatus: Varhaiskasvattajien kokemuksia ulkopuolisen liikuntakasvattajan käyttämisestä varhaiskasvatuksen liikuntakasvatuksessa itäsuomalaisessa kunnassa - Liias, Emmi (2025)
Liias, E. 2025. Physical education in early childhood education – Early childhood educators`experiences of using an external physical education teacher in early childhood sport in an Eastern Finnish municipality. Faculty of Sports and Health Sciences, University of Jyväskylä, Master’s thesis in Sport Pedagogy, 40 pp., 8 appendices.